80 Novel pericardial left ventricular assist device (PAL-VAD) assessment via large animal and cadaveric models. (17th July 2020) - Premawardhana, Amila Diluka; Lodge, Alexander; Sachdev, Siddhant; Karamanavi, Elisavet; Kotecha, Deevia; Mariscalco, Giovanni; Lees, John; Rothman, Alex; Gunn, Julian; Samara-Ratna, Piyal; Adlam, David
Abstract : Background: Cardiogenic shock (CS) is defined as hypotension despite adequate filling status with signs of organ hypoperfusion resulting from a primary cardiac disorder. It complicates 8% of acute myocardial infarctions and, despite the widespread availability of primary percutaneous coronary intervention, continues to have a high short term mortality of 35-50%. Traditional mechanical circulatory support (MCS) can improve cardiac output (CO) however these devices have significant adverse event profiles related to their position within the circulation. PALVAD is an extra circulatory left ventricular assist device, designed to be implanted percutaneously. It provides cardiac support whilst sitting outside the circulatory system in the space between the pericardium and left ventricular (LV) free wall. The dual balloon system connects to a currently external pumping system via a driveline. The actuator (ACT) balloon augments CO through ECG gated LV systolic compression and the positioning balloon sits against the pericardial surface dissipating this force across a large area. Due to its position outside the circulation the device avoids risks with traditional MCS such as clot generation or bleeding (if anticoagulation required), haemolysis and the risk of intravascular infection leading to endocarditis. Furthermore, by avoiding the need for surgical implantation PAL-VAD avoids the risk of general anaesthetic in critically ill patients with the potential to enable more widespread timely initiation of MCS targeting improved outcomes in CS. Purpose: Assess device efficacy in a low CO state in a non-recovery porcine model. Understand device interactions with the left ventricle and pericardium in a cadaveric model. Methodology: Non-recovery porcine model experiments were conducted in ten 40k-60g pigs at a large animal catheterisation facility. In 3 animals a closed chest coronary occlusion reperfusion technique was adopted. In 7 animals an Esmolol infusion was titrated to create a low output state. A Millar catheter was placed in the LV for simultaneous pressure and volume measurements and a Transonic flow probe was placed around the internal carotid for flow measurements. The device was inserted successfully percutaneously and operated for alternating periods of 5 minutes on and 1 minute off. For the cadaveric experiment, the device was inserted into a Thiel embalmed saline or contrast perfused cadaver following which detailed CT and MRI imaging was undertaken with the device in varying configurations. CT images were reconstructed three dimensionally and analysed using NX computer aided design (CAD) software. Results: PAL-VAD had a significant impact across all target parameters with a mean increase of 44% ± 14.5 in CO, 43% ± 16.2 in stroke volume, 25% ± 14.7 in pressure and a 30% ± 18.5 in flow. There was no macroscopic evidence of epicardial or pericardial damage. Cadaveric imaging informed optimal positioning of the device in relation to the LV free wall and a 48% reduction in LV volume was seen when the ACT balloon was inflated. Conclusions: PALVAD performance during a low CO state in non-recovery porcine experiments is promising. Further recovery experiments, including histology assessment, are planned to evaluate safety and efficacy with longer term use to guide optimisation prior to a first-in-man trial. Conflict of Interest: Nil